Biological role of EPS from Pseudomonas syringae pv. syringae UMAF0158 extracellular matrix, focusing on a Psl-like polysaccharide. - Heredia Ponce, Zaira María; Gutiérrez Barranquero, José Antonio; Purtschert-Montenegro, Gabriela; Eberl, Leo; Cazorla-López, Francisco Manuel; De-Vicente-Moreno, Antonio (Springer Nature, 2020)
Pseudomonas syringae is a phytopathogenic model bacterium that is used worldwide to study plant–bacteria interactions and biofilm formation in association with a plant host. Within this species, the syringae pathovar is the most studied due to its wide host range, affecting both, woody and herbaceous plants. In particular, Pseudomonas syringae pv. syringae (Pss) has been previously described as the causal agent of bacterial apical necrosis on mango trees. Pss exhibits major epiphytic traits and virulence factors that improve its epiphytic survival and pathogenicity in mango trees. The cellulose exopolysaccharide has been described as a key component in the development of the biofilm lifestyle of the P. syringae pv. syringae UMAF0158 strain (PssUMAF0158). PssUMAF0158 contains two additional genomic regions that putatively encode for exopolysaccharides such as alginate and a Psl-like polysaccharide. To date, the Psl polysaccharide has only been studied in Pseudomonas aeruginosa, in which it plays an important role during biofilm development. However, its function in plant-associated bacteria is still unknown. To understand how these exopolysaccharides contribute to the biofilm matrix of PssUMAF0158, knockout mutants of genes encoding these putative exopolysaccharides were constructed. Flow-cell chamber experiments revealed that cellulose and the Psl-like polysaccharide constitute a basic scaffold for biofilm architecture in this bacterium. Curiously, the Psl-like polysaccharide of PssUMAF0158 plays a role in virulence similar to what has been described for cellulose. Finally, the impaired swarming motility of the Psl-like exopolysaccharide mutant suggests that this exopolysaccharide may play a role in the motility of PssUMAF0158 over the mango plant surface.
Keywords: Pseudomonas syringae - Genética; Biopelículas; Pseudomonas syringae; Ecología microbiana; Polisacáridos; Biofilm